Acute myeloradiculitis due to cytomegalovirus as the initial manifestation of AIDS. Issue 2 (February 1989) - Mahieux, F; Gray, F; Fenelon, G; Gherardi, R; Adams, D; Guillard, A; Poirier, J
Abstract : A 26 year old male intravenous drug abuser presented with rapidly progressive paraplegia and total incontinence. CSF examination showed elevated protein level and pleocytosis. HIV testing was positive. Anti CMV titres were mildly elevated in serum and CSF. Death occurred 26 days after the onset of neurological signs. Necrotic and inflammatory lesions with numerous inclusion bodies characteristic of CMV were found in the roots of the cauda equina, conus terminalis and lumbar segments of the spinal cord. CMV subependymal encephalitis and HIV encephalitis were also present.